From Theory to Practice: The Impact of Communities of Practice Implementation on Out-Of-School Youth - Pantaleon, Alfred; Bautista, Chester Allan; Villanueva, ZJ; Gundran, Tricia; Fabro, Arrianne Michelle (Journal of Interdisciplinary Perspectives, 2024)
Communities of Practice (CoP) aims to provide services and skills to partner communities while establishing links to communicate learned knowledge to broader groups of people. This study identified and analyzed the impact of communities of practice in Barangay Nagtenga, Sta. Cruz, Ilocos Sur. It used a mixed quantitative and qualitative study approach to evaluate the level of satisfaction of the 18 CoP participants as well as their CoP learning and experience. The data demonstrated high levels of CoP satisfaction, notably with resource speakers and the quality of service provided. Participants shared their learning experiences during the CoP, focusing on knowledge acquisition, skill development, learning transfer to practice, and entrepreneurial management. This study emphasizes the importance of CoPs in empowering marginalized groups and promoting personal and professional development. Recommendations include maintaining and growing CoP initiatives and conducting frequent evaluations to ensure continuous improvement.